Termination of employment for criminal misconduct - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Eishan Jan, Mohammad Naqib (LexisNexis, 2016)
This article discusses the issue related to employee’s criminal misconduct in the workplace and outside of work and termination of employment. More specifically, the following issues are also considered, namely: (a) whether the Industrial Court ought to adjourn its proceedings until after the outcome of the criminal trial in the ordinary court of law for a criminal misconduct at work; and (b) if the answer to question (a) is in the negative, whether the company is to justify the claimant’s dismissal before the Industrial Court independent of the result of the court of law?